PKM Bimbingan Belajar untuk Mengatasi Kesulitan Siswa dalam Mempelajari Matematika - Shofia Hidayah; Arini Hidayati; Alfi Alufiana Sari; Firdatul Azizah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
One of the significant challenges in the world of education is the learning difficulties experienced by students, including in the boarding school environment. The purpose of this service activity is to provide tutoring to grade VII students, especially class VII-C MTs Mambaul Ulum to help students overcome difficulties in learning mathematics. The method of implementing service activities consists of five main stages: 1) planning and preparation including taking care of permits to carry out service activities, conducting initial surveys to identify mathematical materials that are considered necessary for guidance, compiling teaching materials needed in tutoring activities, and determining the schedule for the implementation of tutoring activities; 2) providing pretest questions to determine students' learning abilities before tutoring activities are held; 3) the implementation of tutoring activities; 4) the provision of posttest questions to determine students' mathematics learning ability after tutoring activities, and; 5) evaluation. The results of this activity show that mathematics tutoring activities for grade VII students, especially grade VII-C MTs Mambaul Ulum, have proven to be effective in helping to overcome difficulties in learning mathematics. The increase in the average score from pretest to posttest, from 45 to 80, shows that students are able to understand and master the material taught.